'High profile health facilities can add to your trouble': Women, stigma and un/safe abortion in Kenya. (September 2015) - Izugbara, Chimaraoke O.; Egesa, Carolyne; Okelo, Rispah
Abstract: Public health discourses on safe abortion assume the term to be unambiguous. However, qualitative evidence elicited from Kenyan women treated for complications of unsafe abortion contrasted sharply with public health views of abortion safety. For these women, safe abortion implied pregnancy termination procedures and services that concealed their abortions, shielded them from the law, were cheap and identified through dependable social networks. Participants contested the notion that poor quality abortion procedures and providers are inherently dangerous, asserting them as key to women's preservation of a good self, management of stigma, and protection of their reputation, respect, social relationships, and livelihoods. Greater public health attention to the social dimensions of abortion safety is urgent. Highlights: In public health, trained health personnel and equipped facilities are key to safe abortion. Women did not view poor quality abortion services as inherently dangerous. Safe abortion connoted termination procedures that protect women from poor social outcomes. The social dimensions of abortion safety need more attention.